2018
DOI: 10.1128/mbio.02275-17
|View full text |Cite
|
Sign up to set email alerts
|

A Near-Complete Haplotype-Phased Genome of the Dikaryotic Wheat Stripe Rust FungusPuccinia striiformisf. sp.triticiReveals High Interhaplotype Diversity

Abstract: A long-standing biological question is how evolution has shaped the genomic architecture of dikaryotic fungi. To answer this, high-quality genomic resources that enable haplotype comparisons are essential. Short-read genome assemblies for dikaryotic fungi are highly fragmented and lack haplotype-specific information due to the high heterozygosity and repeat content of these genomes. Here, we present a diploid-aware assembly of the wheat stripe rust fungus Puccinia striiformis f. sp. tritici based on long reads… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
128
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(156 citation statements)
references
References 120 publications
24
128
2
1
Order By: Relevance
“…For each isolate, we predicted about 2,000 effectors on the primary contigs (Supplementary file 4) and haplotigs ( Table 2; Supplementary file 4), respectively, comprising about 8% of the total proteins in each genome, in line with previous reports for Pt Race1, Pst, and Pca (11,18,19). A majority (57-70%) of the effectors belonged to either synteny or chromosome allele pairs, and only 6-9% of the effectors were singletons ( Table 2).…”
Section: Assembly and Annotation Of High Quality Haplotype Phased Ptsupporting
confidence: 85%
See 2 more Smart Citations
“…For each isolate, we predicted about 2,000 effectors on the primary contigs (Supplementary file 4) and haplotigs ( Table 2; Supplementary file 4), respectively, comprising about 8% of the total proteins in each genome, in line with previous reports for Pt Race1, Pst, and Pca (11,18,19). A majority (57-70%) of the effectors belonged to either synteny or chromosome allele pairs, and only 6-9% of the effectors were singletons ( Table 2).…”
Section: Assembly and Annotation Of High Quality Haplotype Phased Ptsupporting
confidence: 85%
“…In summary, our assemblies are clearly significantly better than previously published genome assemblies, for example the Pt Race1 genome (14,818 scaffolds with N50 of 544 kb) (11) and the recently reported genomes of Pst and Pca based on PacBio long-read sequencing (N50 of 1.5 Mb and 268 kb, respectively) (18,19). To date, the three Pt assemblies reported here exhibit the highest level of contiguity and completeness of any rust fungus genome available, providing a fundamental platform for in-depth investigation of the genome function of this destructive pathogen and, more generally, of dikaryotic fungi evolution in the absence of sexual cycle in nature.…”
Section: Assembly and Annotation Of High Quality Haplotype Phased Ptmentioning
confidence: 52%
See 1 more Smart Citation
“…For example, Ustilago maydis , a hemibiotrophic fungal pathogen, secretes the effector Cmu1, affecting salicylic acid (SA) biosynthesis in plants to inhibit SA‐mediated immunity (Djamei et al , ). In contrast with the relatively small set of effectors produced by individual species of bacterial pathogens, whole‐genome sequencing of biotrophic and hemibiotrophic fungi has identified hundreds of potential effectors (Dean et al , ; Duplessis et al , ; Kamper et al , ; Miller et al , ; Nemri et al , ; Pedersen et al , ; Plissonneau et al , ; Schwessinger et al , ; Spanu et al , ; Yoshida et al , ). Functional characterization of fungal effectors is challenging, mainly because fungal effector mutants often display no associated phenotype, either as a result of functional redundancy or of difficulty in accurately measuring small changes in phenotype (Selin et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PacBio sequencing was recently tested to assemble and phase dikaryotic genomes of two rust fungi [17,18]. This research showed that long-read sequencing could resolve challenges for genome assembly of dikaryotic taxa.…”
mentioning
confidence: 99%